Changes in Rice Allelopathy and Rhizosphere Microflora by Inhibiting Rice Phenylalanine Ammonia-lyase Gene Expression - Fang, Changxun; Zhuang, Yuee; Xu, Tiecheng; Li, Yingzhe; Li, Yue; Lin, Wenxiong (Journal of chemical ecology, 2013)
Gene expression of phenylalanine ammonia-lyase (PAL) in allelopathic rice PI312777 was inhibited by RNA interference (RNAi). Transgenic rice showed lower levels of PAL gene expression and PAL activity than wild type rice (WT). The concentrations of phenolic compounds were lower in the root tissues and root exudates of transgenic rice than in those of wild type plants. When barndyardgrass (BYG) was used as the receiver plant, the allelopathic potential of transgenic rice was reduced. The sizes of the bacterial and fungal populations in rice rhizospheric soil at the 3-, 5-, and 7-leaf stages were estimated by using quantitative PCR (qPCR), which showed a decrease in both populations at all stages of leaf development analyzed. However, PI312777 had a larger microbial population than transgenic rice. In addition, in T-RFLP studies, 14 different groups of bacteria were detected in WT and only 6 were detected in transgenic rice. This indicates that there was less rhizospheric bacterial diversity associated with transgenic rice than with WT. These findings collectively suggest that PAL functions as a positive regulator of rice allelopathic potential.